The Long-Term Healthcare Utilization and Economic Burden of RSV Infection in Children ≤5 Years in Japan: Propensity Score Matched Cohort Study - Chirikov, Viktor; Botteman, Marc; Simões, Eric AF (ClinicoEconomics and outcomes research, 2022)
Background: The objective of this study was to estimate the long-term healthcare utilization and cost burden of RSV by chronological age of diagnosis (Year 1, Year 2 and Years 3-5 cohorts) as well as by gestational age at birth in Japan. Methods: The JMDC database was used to retrospectively identify RSV and control patients between February 1, 2011 and January 31, 2016 and follow them through December 31, 2017. Infants with RSV infection (n = 9028 in Year 1; n = 4929 in Year 2; n = 2004 in Years 3-5) were matched to controls (n = 17,886; n = 9351; n = 3655, respectively) based on gestational age and year and quarter of birth; controls were assigned the index date (ie, diagnosis) of their respective match. Covariate-balancing propensity score weights were employed adjusting for remaining imbalances between cohorts. The main outcomes were average cumulative rates for all-cause, asthma/wheezing, and respiratory-related hospitalizations, physician and urgent care/emergency visits and associated costs (reported as 2018 [yen] JPY) over 36-months of follow-up since index. Results: Healthcare utilization was significantly higher among RSV cases for most comparisons. All-cause average differential cost burden was higher for RSV, compared to controls, among the following cohorts: Year 1 full-term ([yen] 277,727); Year 2 preterm ([yen] 530,302), late preterm ([yen] 270,797), full-term ([yen] 238,832); Years 3-5 preterm ([yen] 110,057), late preterm ([yen] 486,670), full-term ([yen] 289,986). While all-cause costs were similar for preterm and late preterm children in the Year 1 cohort, respiratory- and asthma/ wheezing-related attributable costs were substantially higher for RSV. Conclusion: RSV infection had a significant long-term health and economic burden among children infected during their first year of life and later in life. Study findings have import for prevention strategies, currently directed at maternal immunization and monoclonal antibodies for preventing primary RSV infections in the first six months of life and beyond but also for older age not targeted currently. Keywords: respiratory syncytial virus, long-term follow-up, lower respiratory tract infection, prematurity